Evaluation of Supplement Consumption on North Sumatera Regional Police Headquarters Personnel - Munazar; Wiryanto; Khairunnisa (Talenta Publisher, 2020)
The purpose of his study was to determine the factors that influence the consumption pattern of supplements, and to prove the potential interactions of anti-cholesterol, antihypertensive, anti-uric acid, and antidiabetic drugs with supplements. This research is a descriptive research with a survey method. Data collection was carried out on 373 North Sumatera Regional Police Headquarters Personnel. This study used the dependent variable, namely the pattern of supplement consumption, while the independent variables were age, gender, health status, perception, information sources and physical activity. The results of the study using descriptive statistical tests presented using tables and percentages. The results showed that the factors that influenced the pattern of supplement consumption were male (57.1%); 30-49 years old (62.5%); healthy condition (63%); perception as a stamina enhancer (61.7%); sources of information (62.2%) and strenuous physical activity (49.9%). There are synergistic interactions of anti-cholesterol drugs with supplements and antagonistic interactions of antihypertensive, anti-diabetic, anti-gout drugs with supplements.